Comparison of Efficacies of a Blonanserin Transdermal Patch and Blonanserin Oral Formulation for Psychiatric Symptoms in Patients With Schizophrenia Treated With Laxatives Using a Japanese Claims Database - Inada, Ken; Muraoka, Hiroyuki; Matsumoto, Yuji; Fukui, Daisuke; Watanabe, Tomomi; Masuda, Yuriko; Inoue, Sachie; Masuda, Takahiro (Neuropsychopharmacology reports, 2025)
ABSTRACT Background Laxative use has recently been indicated as a risk factor for hospitalization in patients with schizophrenia. Oral antipsychotic therapy for patients with schizophrenia treated with laxatives may be problematic due to gastrointestinal dysfunction, which affects absorption. Therefore, transdermal patches of antipsychotics may be a suitable alternative. We herein compared the efficacies of a blonanserin (BNS) patch and BNS oral formulation in patients with schizophrenia treated with laxatives. Methods A retrospective cohort study was performed using a claims database in Japan provided by DeSC Healthcare Inc. Subjects were BNS patch‐ or BNS oral formulation‐prescribed patients with schizophrenia. The primary outcome was hospitalization to psychiatric wards. The hazard ratio (HR) for hospitalization was estimated using Cox proportional hazards model and adjusted by propensity scores. Results Among the 3896 patients identified, 1407 were prescribed laxatives (BNS patch group: n = 538, BNS oral group: n = 869). Mean ages in the BNS patch and BNS oral groups were 74 and 58 years, respectively. The adjusted HR for hospitalization (BNS patch group vs. BNS oral group) was 1.31 (95% confidence interval; 0.88, 1.94), with no significant difference. Conclusions No significant difference was observed in the risk of hospitalization for patients with schizophrenia treated with laxatives between the BNS patch and BNS oral groups. The effectiveness of antipsychotic patches in these patients warrants further research that considers factors such as patch preference in the elderly. Laxative use has recently been identified as a risk factor for hospitalization in patients with schizophrenia, and oral antipsychotic medication may be problematic due to gastrointestinal dysfunction affecting absorption, suggesting that transdermal antipsychotic patches could be a suitable alternative. A retrospective cohort study compared the efficacies of a blonanserin (BNS) patch and BNS oral formulation in patients with schizophrenia treated with laxatives, with the primary outcome being hospitalization to psychiatric wards. The study found no significant difference in the risk of hospitalization between the BNS patch and BNS oral groups, and further research is warranted to consider factors such as patch preference in the elderly.